Bath dynamics in an exactly solvable qubit model with initial qubit-environment correlations - Ignatyuk, V.V.; Morozov, V.G. (Condensed Matter Physics, 2013)
We study the bath dynamics in the dephasing model of a two-state quantum system (qubit) coupled to an environment of harmonic oscillators. This model was shown [Morozov et al., Phys. Rev. A, 2012 85, 022101] to admit the analytic solution for the qubit and environment dynamics. Using this solution, we derive the exact expression for the bath reduced density matrix in the presence of initial qubit-environment correlations. We obtain the non-equilibrium phonon distribution function and discuss in detail the time behavior of the bath energy. It is shown that only the inclusion of dynamic correlations between the qubit and the bath ensures the proper time behavior of the quantity which may be interpreted as the "environment energy". Проведено дослiдження динамiки термостату у випадку моделi з розфазуванням, що описує дворiвневу квантову систему (кубiт), яка взаємодiє з гармонiчними осциляторами зi свого оточення. Ця модель має аналiтичний розв’язок [Morozov et al., Phys. Rev. A, 2012 85, 022101] як для спiнових змiнних, так i для змiнних термостату. Використовуючи цей розв’язок, отримано аналiтичний вираз для приведеної матрицi густини термостату при наявностi початкових кореляцiй. Отримано нерiвноважну функцiю розподiлу фононiв та детально дослiджено часову еволюцiю енергiї термостату. Показано, що лише належне врахування динамiчних кореляцiй мiж кубiтом та його оточенням забезпечує збереження величини, яку слiд вважати “енергiєю оточення”.